Tailoring diameters of carbon nanofibers with optimal mesopores to remarkably promote hemin adsorption toward ultrasensitive detection of bisphenol A. (30th July 2022) - Zhang, Yuhuan; Chen, Yue; Lei, Yanan; Lu, Hao; Wang, Xingyu; Zhang, Zhong; Li, Jianke
Highlights: Carbon nanofibers (CNFs) with optimal mesopores were synthesized by tailoring diameters to promote hemin adsorption for ultrasensitive detection of BPA. The hemin@CNFs with maximum mesopores ration expressed the highest BPA sensing performance. The hemin@CNFs based BPA sensor was successfully used in sensitive monitoring of BPA in liquors. Abstract: Bisphenol A (BPA) is a worldwide used endocrine disrupting chemical that can migration from food containers and packaging, resulting in bioaccumulation of BPA in humans and causing adverse health effects. Porous electrodes have been proved with large surface areas and high sensing abilities in electrochemical detection of BPA. However, how to tailor the pore sizes to further improve the sensing performance is still a great challenge. Here, we delicately tailored the diameters of carbon nanofibers (CNFs) by adjusting electrospinning parameters to have optimal mesopore structure for strong adsorption of hemin that has been demonstrated with high electrocatalytic activity for BPA sensing. Benefiting from the optimal mesopores structure of CNFs and the synergistic effect of hemin and CNFs, this hemin@CNFs based sensor achieves an ultrahigh sensitivity of 40.97 μA cm −2 μM −1, a low detection limit of 3.1 nM and satisfactory recoveries from 90.2% to 104.2% in the direct detection of BPA in liquors. This work offers a promising sensing platform for ultrasensitive monitoring of BPA.